Patterns of preserved and impaired spatial memory in a case of developmental amnesia - Rosenbaum, R. Shayna; Cassidy, Benjamin N.; Herdman, Katherine A. (Frontiers in Human Neuroscience, 2015)
The hippocampus is believed to have evolved to support allocentric spatial representations of environments as well as the details of personal episodes that occur within them, whereas other brain structures are believed to support complementary egocentric spatial representations. Studies of patients with adult-onset lesions lend support to these distinctions for newly encountered places but suggest that with time and/or experience, schematic aspects of environments can exist independent of the hippocampus. Less clear is the quality of spatial memories acquired in individuals with impaired episodic memory in the context of a hippocampal system that did not develop normally. Here we describe a detailed investigation of the integrity of spatial representations of environments navigated repeatedly over many years in the rare case of H.C., a person with congenital absence of the mammillary bodies and abnormal hippocampal and fornix development. H.C. and controls who had extensive experience navigating the residential and downtown areas known to H.C. were tested on mental navigation tasks that assess the identity, location, and spatial relations among landmarks, and the ability to represent routes. H.C. was able to represent distances and directions between familiar landmarks and provide accurate, though inefficient, route descriptions. However, difficulties producing detailed spatial features on maps and accurately ordering more than two landmarks that are in close proximity to one another along a route suggest a spatial representation that includes only coarse, schematic information that lacks coherence and that cannot be used flexibly. This pattern of performance is considered in the context of other areas of preservation and impairment exhibited by H.C. and suggests that the allocentric-egocentric dichotomy with respect to hippocampal and extended hippocampal system function may need to be reconsidered.